2019
DOI: 10.1021/acs.jchemed.9b00505
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Chemistry Students’ Epistemic Criteria for Scientific Models

Abstract: To engage meaningfully with scientific models, undergraduate students must come to understand what counts as a scientific model and why. To gain a sense of the characteristics that undergraduate chemistry students ascribe to scientific models, we analyzed survey data that address students’ ideas about both model criteria in general and criteria related to specific models of chemical phenomena. The findings suggest that undergraduate general chemistry students possess some productive and some intuitive ideas ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Experts likely (unknowingly) utilize metonymic shortcuts frequently when problem solving, which is relatively innocuous when interacting with peers that are aware of the relevant relationships and assumptions, but these connections need to be made explicit for students. Similar arguments have been made related to the use of models and analogies in chemistry education, where clarity and precision of language is particularly important in terms of being clear regarding their nature, purpose, and limitations. In addition, as alluded to previously, when students are aware of the relevant connections and are able to use metonymic reasoning, it could help reduce the number of ideas they have to manage in their working memory, reducing cognitive load. , Building on the insight provided by cognitive load theory, one potential way to support students is through the use of presenting content using an integrated information approach .…”
Section: Conclusion and Implicationsmentioning
confidence: 69%
“…Experts likely (unknowingly) utilize metonymic shortcuts frequently when problem solving, which is relatively innocuous when interacting with peers that are aware of the relevant relationships and assumptions, but these connections need to be made explicit for students. Similar arguments have been made related to the use of models and analogies in chemistry education, where clarity and precision of language is particularly important in terms of being clear regarding their nature, purpose, and limitations. In addition, as alluded to previously, when students are aware of the relevant connections and are able to use metonymic reasoning, it could help reduce the number of ideas they have to manage in their working memory, reducing cognitive load. , Building on the insight provided by cognitive load theory, one potential way to support students is through the use of presenting content using an integrated information approach .…”
Section: Conclusion and Implicationsmentioning
confidence: 69%
“…This design was intentional, as evidence suggests that the development of metamodeling knowledge is complex and context sensitive. ,, Evidence has shown that students’ ideas about different dimensions of metamodeling knowledge develop independently and that students’ metamodeling ideas may be discipline- or domain-sensitive. , In our previous work, we described qualitative differences in the characteristics of models that students discuss with regard to specific models from their chemistry course compared to scientific models in general. In Lazenby et al, we discussed our observation that students exhibit productive ideas about model characteristics when discussing models in general but are less likely to discuss high-level model criteria when prompted about specific chemical models. Further, students often do not even consider the representations from their chemistry courses to be scientific models at all, particularly those which are mathematical or graphical in nature …”
Section: Discussionmentioning
confidence: 99%
“…14,89 In our previous work, we described qualitative differences in the characteristics of models that students discuss with regard to specific models from their chemistry course compared to scientific models in general. In Lazenby et al, 91 we discussed our observation that students exhibit productive ideas about model characteristics when discussing models in general but are less likely to discuss high-level model criteria when prompted about specific chemical models. Further, students often do not even consider the representations from their chemistry courses to be scientific models at all, particularly those which are mathematical or graphical in nature.…”
Section: Chemical Kinetics: Constructing the Methods Of Initial Ratesmentioning
confidence: 97%
“…The full survey is included in the supplemental information. Findings from remaining questions of the MCS, which focus on students' ideas about characteristics of specific chemical models, are discussed in another manuscript (Lazenby, Rupp, Brandriet, Mauger‐Sonnek, & Becker, ; Lazenby, Stricker, Brandriet, Rupp, & Becker, ).…”
Section: Methodsmentioning
confidence: 99%
“…One potential limitation of the study is our assumption that students' responses to the open‐ended tasks fully represent their epistemic knowledge of the four focal model‐related constructs. Students' ability to articulate their ideas about models and modeling has been shown to be sensitive to context (Gobert et al, ; Krell et al, ; Moritz Krell et al, ; Lazenby, Rupp, et al, ; Lazenby, Stricker, et al, ). As such, students may have possessed knowledge that was not activated by the domain‐general prompts and the written format.…”
Section: Limitationsmentioning
confidence: 99%